Effect of preexercise ingestion of modified cornstarch on substrate oxidation during endurance exercise - Johannsen, N. M.; Sharp, R. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
The purpose of this study was to investigate differences in substrate oxidation between dextrose (DEX) and unmodified (UAMS) and acid/alcohol-modified (MAMS) cornstarches. Seven endurance-trained men (VO2peak = 59.1 ± 5.4 mL·kg-1·min-1) participated in 2 h of exercise (66.4% ± 3.3% VO2peak) 30 min after ingesting 1 g/kg body weight of the experimental carbohydrate or placebo (PLA). Plasma glucose and insulin were elevated after DEX (P < 0.05) compared with UAMS, MAMS, and PLA. Although MAMS and DEX raised carbohydrate oxidation rate through 90 min of exercise, only MAMS persisted throughout 120 min (P < 0.05 compared with all trials). Exogenous-carbohydrate oxidation rate was higher in DEX than in MAMS and UAMS until 90 min of exercise. Acid/alcohol modification resulted in augmented carbohydrate oxidation with a small, sustained increase in exogenous-carbohydrate oxidation rate. MAMS appears to be metabolizable and available for oxidation during exercise.